DATA COLLECTION AS AN EXECUTIVE FUNCTION IN LAW ENFORCEMENT INTELLIGENCE OPERATIONS IN THE REPUBLIC OF SERBIA (Heritage, 2024)
The goal of this research is to identify, scientifically describe, classify and partly explain the weaknesses of data collection as an executive function in law enforcement intelligence operations in the Republic of Serbia using methods of scientific research. The conducted theoretical research identified problems of a functional nature using the executive function of data collection, which can be classified as following problems: 1) theoretical differences in the conceptual determination of data and criminal-intelligence, 2) traditional (reactive) data collection in relation to modern proactive methods, 3) coordination and motivation of police officers, 4) decentralization of the database. Executive functions in criminal-intelligence operations are performed through the criminal-intelligence process, which represents an evidentiary tool for analyzing the actions pertaining to all forms of crime, misdemeanors and other security-related acts, and enables decision-making process based on the collection, processing and analysis of data, as well as undertaking preventive measures. The general purpose of criminal-intelligence operation is to collect data on individuals or organized criminal groups that are involved in criminal activities, in order to gain insight into their functioning.The research was carried out as a theoretical-empirical one, using combination of both theoretical and empirical methods of research (attitudes and opinions of police officers in the police of the Republic of Serbia), that is: general scientific, logical and empirical methods. In this research, the theoretically-empirically confirmed position is that the functioning of the police organization in the Republic of Serbia can be improved, which implies appropriate (functional) changes in its executive functions, including especially changes in the performance of criminal-intelligence operations, i.e. in the collection of data that could contribute  to better development and use of criminal-intelligence outcomes (strategic assessment of public security, operational assessments of public security, profile of a security related problem, profile of a person/group of security interest and other analytical products), which would have impact on the more efficient, effective and economical performance of police work and tasks.The scientific justification of the research derives from its expected results, which can: 1) contribute to the deepening and expansion of scientifically verified knowledge in the field of criminalistics, security and organizational scientific disciplines, 2) indicate the directions, areas and topics of future scientific research and 3) enrich the methodological practice of scientific research on the organization and proactive functioning of the police in contemporary conditions.
Keywords: data collection, criminal-intelligence, executive functions, criminal-intelligence operations, criminal-intelligence outcomes